IFNγ and iNOS-Mediated Alterations in the Bone Marrow and Thymus and Its Impact on Mycobacterium avium-Induced Thymic Atrophy - Barreira-Silva, Palmira; Melo-Miranda, Rita; Nobrega, Claudia; Roque, Susana; Serre-Miranda, Cláudia; Borges, Margarida; Armada, Gisela; de Sá Calçada, Daniela; Behar, Samuel M.; Appelberg, Rui; Correia-Neves, Margarida (Frontiers in Immunology, 2021)
Disseminated infection with the high virulence strain of Mycobacterium avium 25291 leads to progressive thymic atrophy. We previously showed that M. avium-induced thymic atrophy results from increased glucocorticoid levels that synergize with nitric oxide (NO) produced by interferon gamma (IFN) activated macrophages. Where and how these mediators act is not understood. We hypothesized that IFN and NO promote thymic atrophy through their effects on bone marrow (BM) T cell precursors and T cell differentiation in the thymus. We show that M. avium infection cause a reduction in the percentage and number of common lymphoid progenitors (CLP). Additionally, BM precursors from infected mice show an overall impaired ability to reconstitute thymi of RAGKO mice, in part due to IFN. Thymi from infected mice presents an IFN and NO-driven inflammation. When transplanted under the kidney capsule of uninfected mice, thymi from infected mice are unable to sustain T cell differentiation. Finally, we observed increased thymocyte death via apoptosis after infection, independent of both IFN and iNOS; and a decrease on active caspase-3 positive thymocytes, which is not observed in the absence of iNOS expression. Together our data suggests that M. avium-induced thymic atrophy results from a combination of defects mediated by IFN and NO, including alterations in the BM T cell precursors, the thymic structure and the thymocyte differentiation.